Design of Stunting Prevention Education Media Package Based on Technology and Local Wisdom - Lia Nurcahyani; Dyah Widiyastuti; Wiwit Estuti; Arief Tarmansyah Iman; Yeni Fitrianingsih; Fahmi Hafid (Amerta Nutrition)
Background: Stunting leads to increased morbidity and mortality among children. To accelerate stunting reduction, family assistance teams support at-risk families, requiring engaging and accessible educational resources. However, existing educational media materials are fragmented and lack a comprehensive approach, resulting in gaps during family assistance sessions. To improve accessibility and efficacy, a comprehensive, technology-based educational tool is necessary.